Determinación de la concentración óptima de un aditivo orgánico biodegradable fabricado a partir de las cáscaras de naranja para el control de filtrado y mejora de la reología en la formulación de un lodo de inicio base agua a nivel de laboratorio (2021)
Drilling fluids are an essential element in the process of drilling an oil well; it embraces many variables depending on the operation and the right conditions to make it compatible with the formation. Many problems can happen in this process such as an increase in the thickness of the cake, erratic torque, differential sticking and mechanical sticking. The mud formulation can be so expensive due to the many chemical additives used for it to make optimal, for example PAC-LV.